Virtual Reality Application in Rural Tourism Experience: Influence of Authenticity and Tourist Satisfaction. - Aditia Sobarna; Kurniawan Saefullah; Sapari Dwi Hadian (Politeknik Negeri Bandung, 2025)
This study aimed to evaluate the influence of virtual reality (VR) on tourists' perceptions of authenticity and satisfaction within the context of village tourism. Although research on VR tourism has been extensive, specific studies on VR tourism in village settings remain limited, presenting unique challenges due to the distinctiveness of these destinations, often marked by authenticity and natural uniqueness. By involving 385 respondent samples collected through tourism forums and social media platforms in West Java and its surroundings, data collection was conducted from March to April 2024 using purposive sampling. Structural Equation Modelling (SEM) was utilized with SmartPLS to analyze the relationships between inner and outer models. The results indicated that authenticity significantly influenced both the authenticity of activities and objects, which then impacted tourist satisfaction. Furthermore, the study did not find significant differences in satisfaction based on the type of VR devices used, emphasizing the importance of content quality over technical specifications of the device. The theoretical contributions reaffirmed the importance of authenticity in VR tourism experiences, while managerial implications suggested focusing on the development of authentic content to enhance tourist satisfaction in VR tourism. Overall, this research reinforced the critical role of authenticity in VR tourism and provided practical insights for industry practitioners to enhance user experience and promote the maturity of the VR tourism industry.